2022
DOI: 10.1002/ijc.34003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of time to initiation of postoperative radiotherapy after neoadjuvant chemotherapy on the prognosis of breast cancer: A retrospective cohort study in China

Abstract: The optimal time to the initiation of postoperative radiotherapy (TTR) in breast cancer patients after neoadjuvant chemotherapy (NAC) and surgery is unclear.We explored the association between TTR and outcomes among breast cancer females to determine the optimal timing for radiotherapy. We included 1022 women with breast cancer who underwent NAC and surgery between 1997 and 2019. Patients were categorized into three groups based on the TTR: <8 weeks, 8 to 16 weeks and >16 weeks. We used Cox proportional hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…In our study population, the majority of patients started RT within 12 weeks after the last cycle of adjuvant chemotherapy or within 16 weeks after surgery when no adjuvant chemotherapy is given, which is consistent with previous reports (21)(22)(23). In a recent retrospective study of the impact of TTR on survival, among 95 patients treated with NAC without adjuvant chemotherapy, Xie et al (21) reported that 25 (26.3%), 54 (56.8%), and 16 (16.8%) started RT at <8 weeks, 8-16 weeks, and > 16 weeks from surgery, respectively. Compared with early BC patients treated with breast conservation with no indication of adjuvant chemotherapy, TTR is, in general, longer and more heterogenous in the NAT population.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study population, the majority of patients started RT within 12 weeks after the last cycle of adjuvant chemotherapy or within 16 weeks after surgery when no adjuvant chemotherapy is given, which is consistent with previous reports (21)(22)(23). In a recent retrospective study of the impact of TTR on survival, among 95 patients treated with NAC without adjuvant chemotherapy, Xie et al (21) reported that 25 (26.3%), 54 (56.8%), and 16 (16.8%) started RT at <8 weeks, 8-16 weeks, and > 16 weeks from surgery, respectively. Compared with early BC patients treated with breast conservation with no indication of adjuvant chemotherapy, TTR is, in general, longer and more heterogenous in the NAT population.…”
Section: Discussionsupporting
confidence: 92%
“…Our study is not the first one that reports the negative relationship between short TTR and survival outcomes. Xie et al (21) found that TTRs of <8 weeks or >16 weeks were associated with increased risks of BC specific mortality and all-cause mortality compared with the TTR of 8-16 weeks. In another study of patients treated with BCS, TTR >55 days was associated with a higher 10-year DFS (HR = 0.60, 95% CI: 0.38-0.94) and DMFS (HR = 0.64, 95% CI: 0.45-0.92) than TTR < 42 days (26).…”
Section: Discussionmentioning
confidence: 99%
“…In hormone receptor-positive cancer, an interval of no more than 8–12 weeks should be observed [ 32 ]. Regarding adjuvant radiotherapy, the interval should also be kept as short as possible within the first twelve weeks postoperatively [ 27 , 29 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…For an optimal oncological outcome, the timely start of adjuvant treatment is essential [27][28][29]. A meta-analysis from Biagi et al demonstrated a 6% increased risk for death every 4 weeks of delay of the adjuvant chemotherapy [30].…”
Section: Interval Between Surgery and Adjuvant Treatmentmentioning
confidence: 99%
“…For an optimal oncological outcome, the timely start of adjuvant treatment is essential. [27][28][29] Due to severe postoperative complications, initiation of adjuvant chemo-or radiotherapy may be delayed. In our study, we were able to show, that across all types of oncoplstic procedures, patients with NST started adjuvant treatment at the same time as patients undergoing primary surgery.…”
Section: Interval Between Nst and Surgerymentioning
confidence: 99%